Gender differences in dentistry and oral sciences research productivity by researchers in Nigeria - Folayan, Morenike Oluwatoyin; El Tantawi, Maha; Shamsoddin, Erfan; Martínez-Pérez, Guillermo Z. (Frontiers in Oral Health, 2023)
Background: The aim of the study was to assess gender differences in the productivity, impact, collaboration pattern and author position of dentistry and oral sciences researchers in Nigeria. Methods: We examined the Web of Science (WoS) publication records of dentistry and oral sciences researchers to assess gender differences in productivity, impact, collaboration and authorship pattern (first authorship, last authorship and corresponding author). The analysis included the number of publications in journals ranked based on their quartile rating amongst the journals in the subject area (Q1, Q2, Q3 and Q4). Chi square was used to make gender comparisons. Significance was set at >5%. Results: 413 unique authors published 1222 articles on dentistry and oral sciences between 2012 and 2021. The number of WoS documents per female author was significantly higher than that per male author (3.7 vs 2.6, p=0.03). A non-significantly higher percentage of females authored papers in Q2 and Q3 journals and a higher percentage of males authored papers in Q4 journals. The number of citations per female author (25.0 vs 14.9, p=0.04) and the percentage of females listed as first authors (26.6% vs 20.5%, P= 0.048) were statistically greater than men. The percentage of males listed as last authors was statistically greater than females (23.6% vs 17.7%, p=0.04). The correlation between the percentage of papers with researchers listed as first authors and that listed as last authors was not significant for males (p=0.06) but was significant for females (p=0.002). A non-significantly greater percentage of females were listed as corresponding authors (26.4% vs 20.6%) and males were listed as international (27.4% vs 25.1%) and domestic collaborators (46.8% vs 44.7%). Also, there was no statistically significant gender difference in the proportion of articles published in open access journals (52.5% vs 52.0%). Conclusion: Though there were significant gender differences in the productivity, impact, and collaboration profile of dentistry and oral sciences researchers in Nigeria, the higher female research productivity and impact may be driven by cultural gender nuances that needs to be explored further.